Forms of anisotropy for spatial variograms - Budrikaitė, Lina; Dučinskas, Kęstutis (Lietuvos matematikos rinkinys, 2004)
Frequently an observed spatial variable may have anisotropic variability which varies significantly with direction. ln this article overview of anisotropy forms for spatial variograms is presented. Different forms of variograms anisotropy were obtained by fitting salinity data collected at the coastal zone of Baltic Sea. Analysis was carried out using R, a system for statistical computation and graphics.
Keywords: variogram; range; sill; nugget effect; geometric anisotropy; zonal anisotropy